REMAINING LIFE ESTIMATION ON MATERIAL ASTM A297 HP MOD (Nb/MA) BY ULTRASONIC ATTENUATION METHOD AND CREEP STRAIN MEASUREMENT - SUGIHARTO (NIM : 23709004); Tim Pembimbing : Dr. Ir. H. Husaini Ardy; Dr. Ir. Arif Basuki, EKO
Catalyst tubes are reactor where hydrogen (H2) and carbon monoxyde (CO) gases produced from methane (CH4) and water (H2O). The reaction promoted by nickel catalyst. It conducted in endothermis at 35-40 kg/cm2 (gage) pressure and 650-900oC temperature condition. Catalyst tube made from ASTM A297 material, and it designed according to API 530 to avoid creep. Creep in catalyst tube is initiated by micro voids formation. Micro voids linked up together to form micro cracks or fissures. Creep in catalyst tube could be detected by dimensional measurement and ultrasonic attenuation inspection method. However it could not be applied to welding joints. Based on dimensional measurement data said that catalyst tube with creep strain higher than 6% should be replaced. This research found according to the failure record, that catalyst tube could be failed even if the creep strain is less than 6%. When attenuation is less than 6 dB, creep strain and ultrasonic attenuation relationship is linear. But if ultrasonic attenuation is beyond 6 dB, threre are inconsistent corelation between ultrasonic attenuation and creep strain. Ultrasonic attenuation is non destructive inspection method, which is effective in monitoring micro structural change due to creep such as fissures formation. Another result on metallographic examination found that fissures formation occured in the catalyst tube wall if the ultrasonic attenuation higher than 6 dB. Ultrasonic attenuation method can estimate catalyst tube remaining life if the creep strain is less than 6% and attenuation is less than 6 dB. It should give warning mark on catalyst tube which have ultrasonic attenuation higher than 6 dB even if the creep strain less than 6%. Based on this research, ultrasonic attenuation inspection and dimensional measurement are importent role in catalyst tube maintenance, because of the information of metallurgical condition, quality and remaining life estimation.